IEEE 802.11 throughput and delay analysis for mixed real time and normal data traffic - Arenas, Matías (2006)
IEEE 802.11 based network analysis has been largely focused on throughput performance. There has been a growing concern to provide quality of service (QoS) to this protocol suite, the result of which has been the considerable work towards the formulation of the IEEE 802.11e and IEEE 802.11n versions. One important aspect to consider is performance for real time applications like voice over IP (VoIP). In this paper we focus on performance issues of delay and throughput as a function of packet size, initial contention window size settings and the number of active terminals competing for access to the network, when some terminals provide VoIP services, while others transfer data. The simulation model developed using Network Simulator 2 (ns-2) is first validated comparing published results for throughput and delay, to then proceed to perform analysis on Ad hoc networks that will carry mixed VoIP and data traffic. We determine that tuning the initial and final contention window settings on the real time terminals does have a great impact on delay, throughput and packet loss in individual and on the network performance when in congestion.